EFFECT OF GIBBERELLIC ACID AND NITROGEN FERTILIZATION ON GROWTH OF DWARF ARALIA Schefflera arboricola - A. Mukhtar; A. Al-Atrakchii; G. Al-Noaimy (Mesopotamia Journal of Agriculture)
The experiment was conducted with aim to improve the growth of Dwarf Aralias Schefflera arboricola plants, taken from vegetative propagation by apical stem cuttings. The plants sprayed twice with three concentrations of gibberellic acid 0, 100 and 200 mg/L. and fertilized with 0, 150 and 300 mg N/L. by adding 100 ml/15cm standard plastic pot/week. The results showed: The significant largest values of plant height 25.75 cm, internodes length 1.01 cm, total chlorophyll 15.05 mg/g fresh weight and phosphor percentage 0.282%, obtained when plants sprayed with 100 mg/Land fertilized with 300 mg N/l. While spraying plant with 100 and 200 mg/l GA3 only gave significantly largest values of leaves number/plant. On the other hand, significantly higher values of fresh and dry weight of vegetative growth, longest root length, fresh and dry weight of roots obtained when plants fertilized with 300 mg N/l. In general, plants sprayed with 100 mg/L. GA3 and fertilized with 300 mg N/L gave best plants.